The Struggle Is Real: A Systematic Review of Food Insecurity on Postsecondary Education Campuses - Bruening, Meg; Argo, Katy; Payne-Sturges, Devon; Laska, Melissa N. (Journal of the Academy of Nutrition and Dietetics, 2017)
Numerous international studies have examined cross-sectional correlates of food insecurity (FI) among postsecondary education students. Research is needed to synthesize the findings of this work to support vulnerable students. To systematically review peer-reviewed and gray literature to assess the prevalence of FI on postsecondary education institutions, as well as factors related to FI among students and suggested/practiced solutions. Systematic literature review. Medline, Web of Science, and PsycINFO databases were searched for peer-reviewed literature for FI research; a Google search (Google Inc) was conducted to obtain gray literature on FI among postsecondary education students. Undergraduate and graduate students at postsecondary institutions of higher education. Measures included prevalence of FI; sociodemographic, health, and academic factors related to FI; and solutions to address FI on postsecondary institutions. Seventeen peer-reviewed studies and 41 sources of gray literature were identified (out of 11,476 titles). All studies were cross-sectional. Rates of FI were high among students, with average rates across the gray and peer-reviewed literature of 35% and 42%, respectively. FI was consistently associated with financial independence, poor health, and adverse academic outcomes. Suggested solutions to address food security among postsecondary institutions addressed all areas of the socioecologic model, but the solutions most practiced included those in the intrapersonal, interpersonal, and institutional levels. FI is a major public health problem among postsecondary education students. Studies are needed to assess the long-term influence of FI among this vulnerable population. More research is needed on the effectiveness of FI interventions.